The frontiers of executive and judicial power: differences in common law constitutional traditions*. Issue 2 (3rd July 2018) - Mance, Jonathan
ABSTRACT: This article discusses the boundary between the powers of the judiciary, the legislature and the executive branch with regard to issues involving the rule of law and fundamental rights in common law jurisdictions. It examines the different approaches adopted by judges and judiciaries in different common law jurisdictions in handling legislative and executive acts that touch upon fundamental rights, moral issues, and acts of state, and points out that the demarcation of powers among the three branches involves the balancing of different interests which will change with time. Besides, it also concludes that while the constitutional framework and culture of a jurisdiction are important factors determining the role of its judiciary and the limit of judicial power over executive and legislative acts/decisions, it is expected that there will be an increasing consensus on the boundary of judicial power across jurisdictions subscribing to the rule of law and fundamental rights.